Study of Yellow Ginger Jelly Processing - Nguyen , Đặng Mỹ Duyên (Journal of Technical Education Science, 2008)
Ginger is a spicy and medicinal plant. It can be used to treatment or prevent some diseases such as: cold, motion – sick, etc. In this paper, the process of producing ginger jelly is presented. The results were obtained for ginger jelly producing shown that a zingier zerumbet L. with high content of essential volatile oil is the best material for ginger jelly. The optimum conditions of jelly producing were selected such as evaporation temperature, evaporation time and dried mass of ginger. The concentration of extracted ginger solution adding into each batch process was about 6%. In the first studying, we have following results: Zingiber Zerumbet L. with high content of essential volatile oil is the best material for ginger The condition of vacuum evaporating ginger solution: Temperature for evaporating: 70 0 Time for evaporating: 90 Initial concentration dry mass of ginger solution after evaporating: 45%. The ginger solution content: 6%